THE PREVALENCE OF METABOLIC SYNDROME AMONG CHILDREN AND PREVENTIVE MEASURES (World Bulletin of Public Health, 2024)
International studies on metabolic syndrome in school-aged children show that this syndrome is increasing in many developed and developing countries. Metabolic syndrome in children is identified through a combination of risk factors such as abdominal obesity, high blood pressure, dyslipidemia (abnormal blood lipid levels), and elevated blood sugar levels.